2015
DOI: 10.4236/jeas.2015.53010
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Rosemary Essential Oil by Co-Extrusion/Gelling Using Alginate as a Wall Material

Abstract: An essential oil is the volatile lipophilic component extracted from plants. Microencapsulation systems protect the essential oil from degradation and evaporation, and at the same time allow a sustained release. This work analyzed and characterized the rosemary essential oil microcapsules prepared by co-extrusion technique using alginate as wall material and calcium chloride as cross linker. Several instrumental techniques were used: optical microscopy, coulter counter, Fourier transform infrared spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…In the past we tried with Coulter® Counter and we concluded that it is not a good way to determine the size of the alginate microcapsules due to the use of isotonic solution [27].…”
Section: Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…In the past we tried with Coulter® Counter and we concluded that it is not a good way to determine the size of the alginate microcapsules due to the use of isotonic solution [27].…”
Section: Morphologymentioning
confidence: 99%
“…Besides, chitosan has the ability to form hydrogels, dimensional polymeric networks with high water absorption capacity [27], which is very interesting from agricultural point of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained capsules were filtered and washed three times with distilled water in order to remove any solution of cross linking agent that could be remaining in the capsule wall [7].…”
Section: Microencapsulation By Co-extrusion/gellingmentioning
confidence: 99%
“…This technique involves the formation of droplets through a vibration overlay, by passing the solution of the shell material and the active agent through an extruder device, with controlled drip size and speed. These drops fall on a bath containing a solution with the gelling agent, resulting in the formation of capsules [7] [8].…”
Section: Introductionmentioning
confidence: 99%